Teaching AI Literacy for Innovation: Work in Progress - Sengewald, Timon; Tremmel, Agnes (SIGMIS-CPR 2024 - Proceedings of the Computers and People Research Conference: Trust and Legitimacy in Emerging Technologies: Organizational and Societal Implications for People, Places and Power, 2024)
This study addresses the question of how AI literacy could be taught in higher education institutions so that students acquire appropriate competences and skills that will later support them in using AI tools effectively in innovation processes. We used a design science approach to derive learning archetypes to design a corresponding course curriculum. To evaluate these learning archetypes, we had students work on innovation projects in a course and allowed students to use AI tools without restriction. However, the students were required to clearly state how they utilized the AI tools to produce their results. The results indicate that students who were deeply engaged with AI tools outperformed their peers. However, two groups of students were identified who would require different approaches in a course curriculum to potentially increase their AI literacy. While the first group of students underestimated the abilities of AI tools for their given task, the second group overestimated the results and was too early satisfied with them, lacking a certain amount of curiosity.
CRIS-Team Scopus Importer:2024-06-21
Keywords: AI literacy; AI-supported innovation; human-AI collaboration